Determinan Manajemen Laba pada Sektor Transportasi Saat Pandemi COVID-19 - Wahyuni Wahyuni; Ade Maulidianti; Yocelyn Yulianto; Nina Febriana Dosinta (Department of Accounting, Faculty of Economics & Business, 2023)
This study aimed to determine the effect of debt-to-equity ratio, return on equity, return on assets, net profit margin, institutional ownership, ownership concentration, managerial ownership, foreign ownership, free cash flow, company size, board of commissioners meetings, and audit committee meetings on earnings management. The research data was obtained from the annual reports of transportation sector companies listed on the Indonesia Stock Exchange in 2020-2021 using a purposive sampling method of 74 companies. Panel data regression analysis was conducted using Eviews 12. The results of this study indicate that free cash flow and intensive audit committee meetings were able to suppress earnings management practices in companies. However, debt-to-equity ratio, return on equity, return on assets, net profit margin, institutional ownership, ownership concentration, managerial ownership, foreign ownership, company size, and board of commissioners meetings did not have an effect on earnings management.